2022
DOI: 10.3390/bioengineering9090416
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-Based Liquid Metal Materials for Antimicrobial Applications

Abstract: The hazards caused by drug-resistant bacteria are rocketing along with the indiscriminate use of antibiotics. The development of new non-antibiotic antibacterial drugs is urgent. The excellent biocompatibility and diverse multifunctionalities of liquid metal have stimulated the studies of antibacterial application. Several gallium-based antimicrobial agents have been developed based on the mechanism that gallium (a type of liquid metal) ions disorder the normal metabolism of iron ions. Other emerging strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 142 publications
1
9
0
Order By: Relevance
“…Altogether, this data indicates that the Ga droplets, while having a modest antibacterial effect, are not highly effective antibacterial agents in isolation refuting the current assumption in the field that Ga is a robust antimicrobial agent. The mechanism underpinning this modest effect may be through a combination of physical interactions or as more widely reported the release of Ga 3+ ions. , As mentioned previously, solutions containing 2 mg/mL of Ga droplets were found to contain 15 μg/mL of Ga 3+ after 24 h (Figure S5), which is similar to results of previous studies . This indicates that Ga 3+ concentrations above 15 μg/mL are required for substantial antibacterial activity.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Altogether, this data indicates that the Ga droplets, while having a modest antibacterial effect, are not highly effective antibacterial agents in isolation refuting the current assumption in the field that Ga is a robust antimicrobial agent. The mechanism underpinning this modest effect may be through a combination of physical interactions or as more widely reported the release of Ga 3+ ions. , As mentioned previously, solutions containing 2 mg/mL of Ga droplets were found to contain 15 μg/mL of Ga 3+ after 24 h (Figure S5), which is similar to results of previous studies . This indicates that Ga 3+ concentrations above 15 μg/mL are required for substantial antibacterial activity.…”
Section: Resultssupporting
confidence: 85%
“…LMs have gained significant interest in many fields due to their low melting point, possessing both liquid and metallic properties. There is increasing interest in bioapplications of Ga-based LMs, due to their interesting properties and possible interactions. Recently, a few studies have emerged indicating Ga LMs might possess innate antibacterial properties, as well as several recent reviews. Multiple studies have also demonstrated antibacterial applications of Ga LMs in combination with other metals as well as nonmetals. There are several studies that demonstrate antibacterial activity of Ga nanoparticles that are not in the liquid state. , Finally, a few studies also utilize metallic Ga to functionalize phosphate-based glass for antibacterial activity. These studies indicate that the antibacterial mechanism is the release of Ga 3+ ions. According to one study, solid gallium oxide particles (Ga 2 O 3 ) do not exhibit any substantial antibacterial activity against planktonic bacterial cells .…”
Section: Introductionmentioning
confidence: 99%
“…The Ga 3+ in the solution released by liquid metal can permeate into the interior of E. coli cells and enhance the generation of reactive oxygen species (ROS). ROS is the single electron reduction product of oxygen which could induce oxidative damage to DNA and inhibit the division and proliferation of E. coli cells ( Yang et al, 2020 ; Li L. et al, 2021 ; Qu et al, 2022 ). The CFUs of the LM@PU/CNT/LM membrane group were significantly lower than that in the other two groups, which proved that the LM@PU/CNT/LM membrane had an antibacterial effect.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, liquid gallium has attracted extensive attention because of its specific antibacterial activity and biocompatibility, finding wide application in treating hypercalcemia and bone metabolism [7,8]. Continuous accumulation of Ga 3+ in the human body could lead to gastrointestinal diseases, anemia, acute pulmonary inflammation, and an increased probability of tumors [9][10][11][12][13][14][15][16][17]. Another transition metal, palladium, is popular in high-tech fields such as aerospace, fuel cells, and electrical devices by reason of its ductility, electrical conductivity, and corrosion resistance [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%